Letter (copy) : Report of Medical Officer of Health for the Borough of Eastleigh - Tewson, Vincent
1938-07-04 038-0125-002 Secretary's. HVT/FC/DT/611. 4th July, 1938. Mr. J.A. McGuinness, Eastleigh Trades Council, 15, Spencer Road, EASTLEIGH. Dear Mr. McGuinness, REPORT OF MEDICAL OFFICER OF HEALTH FOR THE BOROUGH OF EASTLEIGH. Very many thanks for your letter of the 30th instant enclosing copy of the report of the Medical Officer of Health for the Borough and also copy of the Eastleigh Weekly News dealing with the same matter. I will go through the report carefully as soon as possible, and will also consult members of the Basque Children's Committee, but I feel that probably no useful purpose would be served by entering into controversy on the subject. I feel, however, that the Medical Officer has not spared himself in showing the difficulties of his task, and whilst we are very grateful for all that the Eastleigh Council did in connection with the camp, I think the report could hardly have delved more deeply in the difficulties which were encountered under very extraordinary circumstances. I will return the report to you as soon as possible. Yours sincerely, Assistant Secretary. 292/946/38/125(II)